PENGARUH PERAN ORANG TUA TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELURAHAN TETANDARA KABUPATEN ENDE - Maria Goretty D Bantas; Yasinta Yenita Dhiki; Stefanus Notan Tupen (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2022)
The goal to be achieved in this research is to see the participation of parents in improving children's learning outcomes in mathematics after the pandemic period ends. The research used is descriptive qualitative, the subjects in this study are junior high school students who live in the RT area. 003, RW. 003 Tetandara Village, Ende Regency with a total of 17 people consisting of 9 students and 8 students from different schools and different parents. The results showed that the role given by parents in the mathematics learning process in the form of providing guidance and direction, providing advice, supervising the learning process, and fulfilling children's facilities as students can improve children's learning outcomes in the online mathematics learning process.